A survey of the intraoperative cell salvage in operating rooms at an academic hospital - Yamba, Yemweni Leonard (My University, 2021)
Background Intraoperative cell salvage is a process of collecting shed blood from the surgical field, processing and re-infusing it to the patient. The aim of this study was to retrospectively survey the intraoperative cell salvage practice in the operating rooms at CHBAH over eight months. Methods A contextual, descriptive, retrospective design with consecutive convenience sampling of intraoperative cell salvage records, anaesthetic charts, patients’ files and ICU charts was used. Results Intraoperative cell salvage was used in 50 patients, of which three were excluded as no blood was collected, seven other patients did not progress past the standby mode. Of the 47 patients included in the study, 25 (53.2%) were male, with a median (IQR) age of 33 (27.0 − 44.5) years. Of these patients, the majority, 20 (42.6%) were trauma and 30 (63.8%) were emergency patients. The mean (SD) pre- and postoperative haemoglobin levels of elective and emergency patients was 9.1 (3.3) and 12.0 (2.2) g/dl (p=0.0007) and 10.5 (1.50) g/dl and 10.4 (2.7) g/dl (p=0.8903), respectively. Autologous blood was reinfused in 40 (85.1%) patients. The median blood volume re-infused was similar during emergency (459 ml) and elective (466 ml) surgery. The estimated blood loss of 45 (95.7%) patients was more than 500 ml, with a median of 1 700 ml for emergency and 1 000 ml for elective patients (p=0.0120). Homologous blood was transfused in 30 (63.8%) patients. Two makes of cell saver machines were used and 7 (14.9%) noncatastrophic machine related problems were experienced. Conclusion This study showed that intraoperative cell salvage, although infrequently used at CHBAH, was used predominantly in emergency trauma-related surgeries with few machine-related complications. Intraoperative cell salvage was initiated approximately when the estimated blood loss volume was greater than 500 ml in most surgeries.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology. Johannesburg, 2021